JUBILEE Kul'ziya Konusbayevna Shulembayeva (Experimental biology, 2016)
Doctor of Biological Sciences, Professor of the Department of Genetics and Molecular Biology Al-Farabi Kazakh National University.
Keywords: Jubilee; Kul'ziya Konusbayevna Shulembayeva.